On the effect of the Earth’s magnetic field on the crop-producing power of winter wheat in the territory of Ukraine - M.I. Orlyuk; P. P. Melnik; A. A. Romenets; L. I. Lishchetovich (Геофизический журнал, 2012)
As a result of statistic data treatment a correlation between winter wheat productivity and Earth’s magnetic field intensity on the territory of the Ukraine for the period of 1955-1990 has been revealed. Important spatial variations of the magnetic field as well as temporal ones (B=850 nT for the period of 1955-1990) are observed. Regular raising the level of wheat productivity from Y=17÷18 centners per hectar to Y=32÷35 centners per hectar is registered for studied temporal interval. Obtained correlation coefficients of winter wheat productivity and geomagnetic field for separate regions (that are changing in the limits of r=0,64 for Lugansky region and r=0,89 for Chernovitsky one) as well as for the whole territory of the Ukraine (r=0,85) indicates its considerable dependence from this field.